The use of elder marc in the food industry - L. Ch. Burak (Новые технологии)
The article describes the varieties of elderberry, and the process of black elderberry fruits ripening. External characteristics of flowers, followed by ripening of fruits, have been described. The main components useful for the human body have been identified, which are contained in the fruits of the black elderberry. The effect of elderberry fruits on the human body when used for medicinal purposes has been. Elderberry fruits have a coloring substance that must be added to confectionery creams, sweets, marshmallows, as well as to liqueurs and wine products to give the products color and nutmeg taste. Elderberry fruits can be eaten fresh, ripe, but the most delicious and more useful fruits are provided in processed form, especially in juice and dried form. The useful properties of elderberry have been described, as well as the dangerous properties that appear in case of eating unripe elderberry fruits growing in the Republic of Belarus. The detailed composition of the components of elderberry fruit has been considered, all its useful properties noted. Particular attention is paid to the chemical composition of elderberry fruit, detailed amino acid composition of elderberry fruit has been given, and the composition of anthocyanin content in juice of direct extraction from elderberry fruit has been shown. The use of elderberry pomace in the food industry for the preparation of jam, jams, confiture, preserves and other products, as well as adding to wine, alcoholic beverages, to impart nutmeg taste, in the confectionery industry to add to dough and giving the product an almond smell has been described. It is especially noted that the pomace from elderberries contains biological active substances, bioflavonoids, anthocyanins, which confirms their immediate importance and the need to use for the creation of many products for preventive and functional purposes in the food industry.